Interactive effects of workplace ostracism and belief in reciprocity on fear of negative evaluation - Qura-tul-aain Khair; Tasneem Fatima (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
Workplace mistreatment is although one of crucial reality of organization's life that exists inevitably but it may possess certain potential in collaboration with other variables to act into prosocial behaviors. Based on affective events theory (AET) this research study attempts to investigate the impact of workplace ostracism on employees' fear of negative evaluation. This model explains that workplace ostracism could lead to employees' fear of negative evaluation but belief in reciprocity as moderator has property to weaken this relationship. In an environment of workplace mistreatment, the belief in reciprocity actually sets the degree of employees' understanding to avoid fear of negative evaluation by considering themselves responsible first for workplace mistreatment. Data was collected from education sector of Pakistan, comprising faculty and non-faculty members working at different hierarchical levels in public and private school, colleges and universities. Results have confirmed our hypotheses and found the moderating impacts of belief in reciprocity on the relationship between workplace ostracism and fear of negative evaluation. This paper has used SPSS and AMOS tools for data analysis. For practical implication, managers can use implicit property of belief in reciprocity strategically in the interest of organization and employees. According to which belief in reciprocity creates the awareness and direct one's attention towards previous actions of one-self.
Keywords: 330; workplace ostracism; fear of negative evaluation; belief in reciprocity; affective events theory